Soybean Ferritin: Isolation, Characterization, and Free Radical Generation F - Galatro, Andrea Verónica (2012)
The main aim of this work was to assess the multi-task role of ferritin (Ft) in the oxidative metabolism of soybean (Glycine max). Soybean seeds incubated for 24 h yielded 41 ± 5 microg Ft/g fresh weight. The rate of in vitro incorporation of iron (Fe) into Ft was tested by supplementing the reaction medium with physiological Fe chelators. The control rate, observed in the presence of 100 microM Fe, was not significantly different from the values observed in the presence of 100 microM Fe-his. However, it was significantly higher in the presence of 100 microM Fe-citrate (approximately 4.5-fold) or of 100 microM Fe-ATP (approximately 14-fold). Moreover, a substantial decrease in the Trp-dependent fluorescence of the Ft protein was determined during Fe uptake from Fe-citrate, as compared with the control. On the other hand, Ft addition to homogenates from soybean embryonic axes reduced endogenously generated ascorbyl radical, according to its capacity for Fe uptake. The data presented here suggest that Ft could be involved in the generation of free radicals, such as hydroxyl radical, by Fe-catalyzed reactions. Moreover, the scavenging of these radicals by Ft itself could then lead to protein damage. However, Ft could also prevent cellular damage by the uptake of catalytically active Fe.